"Wind energy is not an issue for government": Barriers to wind energy development in Newfoundland and Labrador, Canada. (September 2017) - Mercer, Nicholas; Sabau, Gabriela; Klinke, Andreas
Abstract: Despite having amongst the strongest potential for wind energy development (WED) of any jurisdiction in North America, the Canadian province of Newfoundland and Labrador (NL) remains dependent on fossil fuels for economic activity, government revenue, as well as electricity generation. The study is a comprehensive assessment of barriers to renewable energy development in NL, with a focus on wind energy. While NL is chosen as the primary case study, the study's theoretical breadth provides insights for other renewable energy (RE) development and policy contexts as well. Seventeen semi-structured expert interviews were conducted with respondents from academia, community groups, government, and the private sector. An analytical framework was employed and directed content analysis was utilized. A large majority of expert respondents (65%) classified the current state of WED in the province as 'unfavourable'. In total, 19 unique barriers were identified; the most significant barriers to WED were found to be political (71% of respondents), economic (65%), as well as related to lack of knowledge and agreement (53 and 41%, respectively). The study demonstrates that there is no single barrier to the development of RE sources; as such, comprehensive policy solutions comprised of financial, educational, legislative, and consultative components are required. Highlights: Trudgill's (1990) 'AKTESP' analytical framework is applied to identify and explain perceived barriers to wind energy. Stakeholders perceived political, economic, and knowledge barriers as the most significant. Stakeholders did not view technological and social barriers as insuperable. Study concludes barriers are multifaceted; comprehensive policy solutions are required.